2005
DOI: 10.1103/physrevlett.94.184502
|View full text |Cite
|
Sign up to set email alerts
|

Scaling and Instabilities in Bubble Pinch-Off

Abstract: We have used a 100 000 frame-per-second video to analyze the pinch-off of nitrogen gas bubbles in fluids with a wide range of viscosity. If the external fluid is highly viscous (eta(ext)>100 cP), the bubble neck radius is proportional to the time before break, tau, and decreases smoothly to zero. If the external fluid has low viscosity (eta(ext)<10 cP), the radius scales as tau(1/2) until an instability develops in the gas bubble, which causes the neck to rupture and tear apart. Finally, if the viscosity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

31
182
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(214 citation statements)
references
References 15 publications
31
182
1
Order By: Relevance
“…The data are well fit with a power law: h min ∝ τ α h , with α h = 0.56 ± 0.03. This is consistent with simulations of Leppinen et al who found α h ≈ 0.55 [25] but exclude α h = 0.50 [21,22,23]. Our data cannot distinguish pure power-law behavior with α h = 0.56 (solid lines in Fig.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…The data are well fit with a power law: h min ∝ τ α h , with α h = 0.56 ± 0.03. This is consistent with simulations of Leppinen et al who found α h ≈ 0.55 [25] but exclude α h = 0.50 [21,22,23]. Our data cannot distinguish pure power-law behavior with α h = 0.56 (solid lines in Fig.…”
supporting
confidence: 92%
“…Other singularities [1] have been shown to be sensitive to noise [2]. However, experiment and theory up to now have ignored cylindrical asymmetry [21,22,23,24,25,26], or could not show it to be a generic feature of breakup [14]. We have shown that tilting the nozzle by just 0.07 • detectably alters the outcome of breakup.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Simultaneously, a ring of higher pressure develops around the neck of the elongation by the inflow of liquid compressing the neck. Upon neck closure (Burton, Waldrep & Taborek 2005;Thoroddsen, Etoh & Takehara 2007) the liquid between the separated neck parts is accelerated upwards into bubble 2 and downwards through the separated neck part. Immediately after closure, the elongation of bubble 2 still has a sharp, singularity-like tip, and the jet emerging from this tip must be extremely thin and fast.…”
Section: Jet Dynamicsmentioning
confidence: 99%